Urban Digital Twin and Energy Modeling – Experiences and case study analyses - Danila Longo; Beatrice Turillazzi; Rossella Roversi; Stefano Lilla; Carlo Alberto Nucci; Andrea Costa; Alessandro Piccinini (Agathón)
The transition towards sustainable and digital cities is a complex challenge with crucial implications for citizen well-being. In this context, the concept of an Urban Digital Twin (UDT) emerges as an innovative resource, although the methodologies and technologies applied are still at an initial stage. This article explores the use of the UDT in the context of energy transition, focusing on the experience of Bologna, an Italian city committed to climate neutrality by 2030. Experimentation in specific case studies demonstrates how the UDT enables data analysis and scenario simulation to optimise energy efficiency and promote decarbonisation, facilitates data collection and integration, overcomes privacy issues, and enables multi-stakeholder governance.